2014
DOI: 10.1016/j.ygeno.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the Ophiocordyceps sinensis fruiting body reveals putative genes involved in fruiting body development and cordycepin biosynthesis

Abstract: Ophiocordyceps sinensis is a highly valuable and popular medicinal fungus used as a tonic and roborant for thousands of years in traditional Asian medicine. However, unsustainable harvesting practices have endangered this species and very little is known about its developmental programming, its biochemistry and genetics. To begin to address this, the transcriptome of the medicinal O. sinensis fruiting body was analyzed by high-throughput. In this O. sinensis 454-EST dataset, four mating type genes and 121 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 41 publications
2
72
0
Order By: Relevance
“…Even more surprisingly, a total of 12,980 unigenes were found to be expressed in cultured mycelia of the species in a recent study (Liu et al, 2015). The secondary metabolism clusters were largely conserved between O. sinensis and other insect pathogens (Hu et al, 2013) and enzymes associated with carbohydrate metabolism were found to be expressed (Xiang et al, 2014). The identified pseudogenes should be re-evaluated to check whether the fungus has really lost the relevant function or whether functional paralogs can be found in the genome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even more surprisingly, a total of 12,980 unigenes were found to be expressed in cultured mycelia of the species in a recent study (Liu et al, 2015). The secondary metabolism clusters were largely conserved between O. sinensis and other insect pathogens (Hu et al, 2013) and enzymes associated with carbohydrate metabolism were found to be expressed (Xiang et al, 2014). The identified pseudogenes should be re-evaluated to check whether the fungus has really lost the relevant function or whether functional paralogs can be found in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Obligate biotrophs may have lost some metabolic pathways, including the metabolism of inorganic nitrogen, inorganic sulfur and thiamine, and genes encoding carbohydrate active enzymes and secondary metabolism enzyme (Baxter et al, 2010;Spanu, 2012). However, the transcriptome analyses using EST library sequencing of stroma of O. sinensis revealed more expressed genes (9,641) (Xiang et al, 2014) than the genome prediction by Hu et al (2013). Even more surprisingly, a total of 12,980 unigenes were found to be expressed in cultured mycelia of the species in a recent study (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fruiting body mutants are now available for many fungi other than P. anserina, including Sordaria macrospora [27], N. crassa [28], A. nidulans [29] and Coprinopsis cinerea (formely Coprinus cinereus) [30,31] and could be analyzed using similar methods. They are complementary to the now more widespread large scale analyses of transcriptomes during fruiting body development as performed in the ascomycetes Fusarium graminearum and Fusarium verticilloides [32][33][34], N. crassa [35,36], S. macrospora [37], Pyronema confluens [38], Tuber melanosporum [39][40][41], Cordyceps militaris [42] and Ophiocordyceps sinensis [43], as well as in the basidiomycetes C. cinerea [44], Moniliophthora perniciosa [45], Agrocybe aegerita [46], Lentinula edodes [47,48], Auricularia polytricha [49] and Ganoderma lucidum [50].…”
Section: Resultsmentioning
confidence: 99%